"(Meth) Will Hurt You and Hurt Your Teeth": Teen, Parent, and Dental Practitioner Perspectives on Implementing Crystal Meth Use Prevention Messaging in the Dental Office Setting. (4th May 2022) - Skeer, Margie R.; Landy, David M.; Ryan, Emma C.; Lee-Bravatti, Michelle; Boyadjian, Tamar; Towers, Jennifer
Abstract : Objectives . Crystal methamphetamine ("meth") use among youth living in rural areas is higher than the national average. Given how drastically meth affects teeth (i.e., "meth mouth"), engaging dental professionals as one of multiple channels in rural areas to deliver meth prevention messaging is a novel approach. The objective of this research was to assess the feasibility and acceptability of incorporating meth use prevention messaging into dental visits with teenagers. Methods . We conducted phenomenological, qualitative research with dental practitioners, teens, and parents/guardians in three communities in North Idaho, from 2015 to 2016. We recruited practitioners using a snowball sampling strategy and placed phone calls to dental practices and contacted teens and parents through schools, libraries, local sporting events, and word-of-mouth. Using NVivo 12-Plus, parent- and teen-specific codebooks and themes were developed from guides and transcripts. Transcripts of the dentists and hygienists were reviewed to ascertain the main ideas and themes. Results . Overall, practitioner, teen, and parent participants viewed meth prevention messages delivered by dental professionals as acceptable and feasible. Compared to those in private practice, public health dental providers were invested in meth prevention and were eager to help. Barriers to overall acceptability and feasibility included hygienists' low self-efficacy to deliver a communication-based intervention, infrequency of dental visits impacting the ability to reach enough teens through this venue, and the fact that teens could feel "targeted" by providers. Teens also raised concerns about scary messages exacerbating preexisting dental visit anxiety. Facilitators included the following: dental practitioners already engaging in health education with their patients, parents, and teens seeing dental professionals as appropriate purveyors of antimeth messaging and support for increased meth prevention efforts given the impact of meth use in their communities. Conclusions . Well-crafted, developmentally appropriate meth prevention messages would likely be well received by teens and supported by parents in dental offices. These data are being used to develop a novel, theory-based communication and behavioral strategy to integrate dental professionals into the delivery of messages aimed at preventing the initiation of meth use among rural Idaho teens.